Targeting Inflammation in Bronchiectasis. - Mac,Aogáin M; Gilmour,A; Chalmers,JD; Chotirmall,SH (Drugs, 2026)
Bronchiectasis is defined by chronic infection, dysregulated inflammation and impaired mucociliary clearance underpinning progressive structural lung injury. While airway infection remains a clinical hallmark, numerous studies demonstrate that excessive neutrophil-dominated inflammation is a key determinant of disease severity, exacerbation risk and quality of life. Recent developments have transformed our understanding of inflammatory drivers uncovering distinct inflammatory endotypes defined by dominant microbial species, pattern-recognition receptor activation, inflammasome signalling, Th17-associated cytokine networks and failures of mucosal immunity. The emerging roles of viral-bacterial interactions, fungi, pathobionts and the broader microbiome challenge the conventional infection-only paradigm and highlight gaps in current therapeutic strategies. Such developments underpin the rationale behind anti-inflammatory strategies in bronchiectasis, ranging from suppression of neutrophil-driven injury through direct neutrophil elastase or upstream dipeptidyl peptidase-1 (DPP-1) inhibition, to immunomodulatory macrolides, toward therapies aimed at recalibrating epithelial and mucosal homeostasis. While several antibacterial and anti-infective trials have produced mixed results, this is likely to reflect unresolved heterogeneity in microbiome composition and host immune signalling. In contrast, emerging anti-inflammatory strategies show strong positive signals, reinforcing the need for better endotyping and biomarker-guided patient selection. Here we synthesize recent mechanistic and clinical insights to propose a more integrated framework for understanding and ultimately targeting airway inflammation in bronchiectasis.